Kajian parameter gender dalam substansi peraturan perundang-undangan di Indonesia - Kadek Wiwik Indrayanti (University of Merdeka Malang, 2021)
This article examines the objectives, principles, and integration of gender equality indicators in the formulation of laws. The method used is normative legal research because it examines some of the substance of laws that are gender biased. The results show that the role of the government in realizing gender equality in Indonesia today has been carried out through laws and regulations, policies and programs but still has to be fought for because in reality there is still a gap between the two sexes, which has an impact on gender discrimination. There are several laws whose substance shows discrimination against women, such as the Marriage Law. Therefore, the concept of gender equality should be understood as a